Analisis Sertifikasi Halal Bagi Produk Pangan di Indonesia - Yanuardin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Halal food product certification is an important effort to ensure that products consumed by Muslims comply with Islamic sharia law. This certification process involves various stages and requires an in-depth understanding of the halal requirements set by the relevant authority institutions. This research aims to analyze the certification procedures for halal food products, the factors that influence the success of certification, as well as the implications of certification for producers and consumers. The research method used is literature study and descriptive analysis with reference to international and national halal regulations and standards, such as those issued by the Institute for the Study of Food, Drugs and Cosmetics, the Indonesian Ulema Council (LPPOM MUI) in Indonesia. The analysis results show that there are several main components in the halal certification process, namely: raw material assessment, production process, packaging and storage, audit and inspection.